Discrimination Against Foreigners in Japan - Kostina Ekaterina (Universitas Internasional Batam, 2017)
The notion of Japan as a homogeneous society has been challenged by many recent studies. In fact, Japan is a home to different minority groups, ethnic and non-ethnic. Although the percentage of resident foreigners is relatively low comparing to other countries, acts of racial discrimination against them occur in everyday life in Japan. Thus, this study discusses how the foreigners are treated in Japan, and therefore tends to answer the question whether the legislation exists in order to protect their rights and penalize discriminatory activities committed by citizens or organizations. The study reveals that although Japan signed the UN Convention on the Elimination of Racial Discrimination (CERD), the problem of racial discrimination against foreign nationals still remains considerable. There are many reported incidents of human rights violation and discrimination practice against foreigners among individuals due to differences in language, religion, custom and appearance as well. Some of the cases handled by the human rights organs of the Ministry of Justice include the refusals of apartment rental or entrance to a public swimming pool on the grounds of being a foreigner. The study suggests that Japan should introduce new legislation to combat discrimination. === Pendapat yang menyatakan bahwa Jepang adalah masyarakat homogen telah dibantah oleh banyak penelitian. Kenyataannya, Jepang adalah rumah bagi berbagai kelompok minoritas, etnis dan non etnis yang berbeda-beda. Meskipun persentase orang asing relatif rendah dibandingkan dengan negara lainnya, tindakan diskriminasi rasial terjadi dalam kehidupan sehari-hari di Jepang. Oleh karena itu, studi ini membahas bagaimana perlakuan terhadap orang asing di Jepang dan menjawab pertanyaan apakah peraturan perundang-undangan yang ada mampu memberikan perlindungan hak dan menindak kegiatan diskriminasi yang dilakukan oleh warga masyarakat dan organisasi. Studi ini mengungkapkan bahwa meskipun Jepang telah menandatangani Konvensi PBB tentang Penghapusan Diskriminasi Rasial, permasalahan diskriminasi rasial terhadap warga negara asing masih sering terjadi. Berbagai peristiwa telah dilaporkan terkait pelanggaran hak asasi manusia dan praktek diskriminasi terhadap orang asing yang disebabkan karena perbedaan bahasa, agama, kebiasaan dan juga penampilan. Beberapa dari kasus tersebut ditangani oleh badan hak asasi manusia dari Kementerian Kehakiman termasuk penolakan penyewaan apartemen atau larangan masuk ke tempat permandian umum bagi orang asing. Studi ini menyarankan agar Jepang menerbitkan hukum yang baru yang menentang diskriminasi.